Karnali Academy of Health Sciences - Clearing Out Karnali’s Limbo and yet more to go. - Bhattarai, Ramesh; Rawal, Mangal (Journal of Karnali Academy of Health Sciences, 2022)
When a pregnant woman was being carried in a DOKO through the treacherous landscape in search of medical help, who had ever thought that the province will be producing doctors for the country someday, and yes the day came. However, it is a matter of great pride that the province where the health personnel used to feel disappointed when being placed, now produces the same manpower that can be placed all over the country. KAHS is working to uplift health services, education, and medical research in the Karnali region for a decade. Now, it has become the only center in the province to run five bachelor’s and four master’s level health education programs including MBBS and MD/MS. The five bachelor programs are MBBS, BPH, BMS, BNS, and BPharm, and four post-graduate level MD/MS programs in Pediatrics, Anesthesiology, General Practice, Emergency Medicine, and Orthopedics. Furthermore, MD/MS in Gynae./Obs., Surgery, Basic Medical Sciences like Anatomy, Physiology, etc., MPH (Master of Public Health), MSc Epidemiology, and MN (Master of Nursing) are in the process of taking approval from the medical education commission (MEC) in the following years. KAHS has been working in the field of quality health care service to fulfill the constitutional provision of Nepal which states that every citizen shall have equal rights for free basic health services, and no one shall be deprived of emergency health care services.1 KAHS was established on October 20, 2011 (2068/07/03), by an Act of the parliament of Nepal by upgrading the existing